2020
DOI: 10.3390/atmos11121330
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Snow Depth, Snow Cover Duration, and Potential Snowmaking Conditions in Austria, 1961–2020—A Model Based Approach

Abstract: We used the spatially distributed and physically based snow cover model SNOWGRID-CL to derive daily grids of natural snow conditions and snowmaking potential at a spatial resolution of 1 × 1 km for Austria for the period 1961–2020 validated against homogenized long-term snow observations. Meteorological driving data consists of recently created gridded observation-based datasets of air temperature, precipitation, and evapotranspiration at the same resolution that takes into account the high variability of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 52 publications
6
48
0
1
Order By: Relevance
“…In this regard, artificial snow production and snowmaking on ski slopes are increasingly used. However, climate warming also reduces the hours of possible operation of snowmaking devices (snow cannons) on slopes during winter periods [2]. In this work, the calculation of the possible number of hours of operation of snow guns and their change in the winter periods of the last decade for the slopes of the Moscow region is revealed.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this regard, artificial snow production and snowmaking on ski slopes are increasingly used. However, climate warming also reduces the hours of possible operation of snowmaking devices (snow cannons) on slopes during winter periods [2]. In this work, the calculation of the possible number of hours of operation of snow guns and their change in the winter periods of the last decade for the slopes of the Moscow region is revealed.…”
Section: Methodsmentioning
confidence: 98%
“…The calculation of the number of hours suitable for the operation of snowmaking devices in the winter periods of the last decade was carried out on the basis of meteorological data from the site rp5.ru [7] on the basis of the rule from [2]. According to this rule, weather conditions with a wet bulb temperature not exceeding −4 • C are suitable for snowmaking.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown a general decrease in snow depth and snow cover duration since the end of the 1980s throughout the European Alps [26,27] and Pyrenees [28]. This shortens the ski season, which affects the condition of local tourism [29] and businesses [30]. A similar situation applies to the Polish Tatra mountains [31] and Carpathians due to the climate warming [32].…”
Section: Artificial Snow Production From Reclaimed Watermentioning
confidence: 95%
“…It is well documented that the climate is changing [1][2][3]. Impacts are seen as globally rising temperatures [2,4] with a reduced number of cold days and nights and an increased number of warm days and nights [4], an altered depth [5][6][7] and duration of snow and ice cover [6][7][8], changing precipitation [4,[9][10][11] and river flow regimes [12][13][14], or an increased number of extreme events [2,4,15]. However, the magnitude and impact direction of major climate variables, such as temperature, precipitation, catchment runoff, and evapotranspiration in both climate observations and projections vary significantly at the global and regional scale [16,17].…”
Section: Introductionmentioning
confidence: 99%